Peran Guru dalam Pembelajaran Teks Deskripsi di Sekolah Dasar - Utari, Nisa Ria; Fadilah, Mutia Kansa Al; Sarah, Sarah; Nuraeni, Siti; Ramadhan, Dian; Ayuandina, Ayuandina; Julianto, Indra Rasyid (Jurnal Cahaya Edukasi, 2025)
Descriptive text is a text that describes a fact based on the sense of sight. This text serves to stimulate children's mindset based on what they observe/experience in an object. Therefore, students need the role of a teacher in order to achieve learning objectives. The teacher plays an important role as a motivator and facilitator, so that students have no difficulty in achieving learning goals. In description text learning, the teacher plays an important role as a motivator and facilitator where a motivator is to provide a motivation for learning, especially in description text learning. In this study, researchers focused on the role of teachers in descriptive text learning. The research used qualitative descriptive method to find in-depth information about the role of teachers in learning descriptive text. In addition, researchers used an interview system to explore relevant information. In the interview, the teacher stated that media and methods play an important role in a learning process, especially in learning descriptive text.